Elemen Sukses Penerapan Dynamic Governance di Provinsi Jawa Barat - Martoyo Martoyo; Nahot Tua Parlindungan Sihaloho (Jurnal Public Policy, 2021)
The purpose of this study is to explore and analyze the variables that determine the success of implementing dynamic governance in West Java. This research was conducted qualitatively using a literature review research design. The data obtained were then analyzed following the steps of qualitative data analysis by Miles, Huberman & Saldana. The results of this study reveal that there are at least four elements that contribute significantly to the success of dynamic governance in West Java, namely the typical pentahelix collaboration, creative funding, digital government, and the Jabar Open Data program. The implications of this study confirm two things. First, program forms in dynamic governance are based on problems in the local environment, so that each region has a different type of program. It's just that in principle the program must be adaptive and accommodating. Second, the design of dynamic governance is the most reliable design for the needs and conditions of the people of West Java today. It could be that the design of agile governance will be adopted by the West Java Provincial Government when dynamic governance is deemed irrelevant and unsolvable.